Experimental study and performance evaluation of the renewable energy conversion systems under realistic grid conditions using RTDS - Sattar, A.; Muyeen, S.M.; Al-Durra, A.; Caruana, C.; Musleh, A. (2016)
This paper presents a new approach to analyze the steady-state and transient behavior of grid connected renewable energy sources. For this case, a permanent magnet generator based variable speed wind turbine interfaced to the grid through back to back fully rated converters is considered. The salient feature of this paper is the introduction of the realistic grid into real time digital simulation such that practical effects can be examined prior to the experimental test stage. The effect of power quality phenomena present on the supply voltage waveforms on the performance of the variable speed wind turbine system is examined. It is noted that tuning the grid side converter voltage loop for successful low voltage transient operation might not be sufficient for operation under the non-ideal voltage waveforms of actual grids. Simulation and hardware implementation have been carried out by RTDS/RSCAD.